Gli spazi di accoglienza multireligiosa nel sistema universitario italiano (Stato, Chiese e pluralismo confessionale, 2024)
Multi-religious Welcoming Spaces in the Italian University SystemABSTRACT: The essay deals with the issue of the spaces Italian universities provide for worship and other spiritual activities. Designating public spaces for religious and spiritual needs is an example of the ongoing adaptation process of institutions to social needs that is marked by ever-increasing religious and cultural pluralism. However, Italian universities have been affected by this phenomenon only in a marginal way so far. This paper, which is based on field research, describes the similarities and differences of the solutions adopted in various Italian institutions of higher education. In her concluding remarks, the Author points out the emergence of the “Islamic Question”. Indeed, the attitude towards Muslim communities by Italian universities is very similar to that of other public administrations.SOMMARIO: 1. Introduzione: pluralismo religioso e identità nella comunità studentesca universitaria italiana - 2. Gli spazi universitari di accoglienza della diversità religiosa - 3. Stanze multireligiose nel sistema universitario italiano: unapreliminare e frastagliata mappatura - 4. L’accoglienza multireligiosa nel sistema universitario: uno specchio delle dinamiche italiane fra Stato e confessioni religiose? Brevi conclusioni.